2012
DOI: 10.1007/s00213-012-2870-2
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the behavioral effects of morphine in rats by serotonin (5-HT)1A and 5-HT2A receptor agonists: antinociception, drug discrimination, and locomotor activity

Abstract: Rationale Indirect-acting serotonin (5-HT) receptor agonists can enhance the antinociceptive effects of morphine; however, the specific 5-HT receptor subtype(s) mediating this enhancement is not established. Objective This study examined interactions between morphine and both 5-HT1A and 5-HT2A receptor agonists in rats using measures of antinociception (radiant heat tail flick and warm water tail withdrawal), drug discrimination (3.2 mg/kg morphine versus saline), and locomotion. Methods Male Sprague-Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…When RO5263397 was studied in combination with cocaine, RO5263397 was injected immediately before the animals were put into the test chambers and a dose of cocaine (15 mg/kg) was administered 20 min (habituation period) later, which was followed by a 60 min test period. A separate experiment also examined the effect of RO5263397 on the dose-effect curve of cocaine by using a cumulative dosing procedure [9]. For this experiment, RO5263397 was administered immediately prior to the start of the test session and different doses of cocaine (cumulative doses of 3.2, 10, 32 mg/kg) were given at times 20 min, 40 min and 60 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When RO5263397 was studied in combination with cocaine, RO5263397 was injected immediately before the animals were put into the test chambers and a dose of cocaine (15 mg/kg) was administered 20 min (habituation period) later, which was followed by a 60 min test period. A separate experiment also examined the effect of RO5263397 on the dose-effect curve of cocaine by using a cumulative dosing procedure [9]. For this experiment, RO5263397 was administered immediately prior to the start of the test session and different doses of cocaine (cumulative doses of 3.2, 10, 32 mg/kg) were given at times 20 min, 40 min and 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…The locomotor effects of each dose of cocaine were recorded for 20 min but for each dose the data from the first 5 min immediately after the drug injection were discarded because the rats always demonstrated a brief hyperactivity due to handling and injection. This procedure generates highly consistent and reliable dose response curves of drugs such as morphine, cocaine and methamphetamine [2, 9, 15]. …”
Section: Methodsmentioning
confidence: 99%
“…Function of HTR3A was implicated in alcohol addiction (Shorter and Kosten 2011) and the association of the HTR1B gene variant was found with heroin dependence among Han Chinese (Gao and others 2011). Indirect-acting HTR receptor agonists can enhance the antinociceptive effects of morphine although the specific subtype(s) mediating this enhancement is not established (Li and others 2012). Many drugs target the serotonin system, including Vilazodone that was approved by the United States Food and Drug Administration (informally USFDA) in 2011 for depression (Bach and Arango 2012), Methoxectamine, a HTR2 agonist currently being explored as a fast-acting antidepressant, and Rotundine, currently used in China to treat cocaine addiction (Hagan and others 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the response rate in po morphine at 30 mg/kg tended to decrease. Morphine shows sufficient antinociceptive effects in a tail-flick test at 30 mg/kg by po (Okura et al, 2008), at 3 or 10 mg/kg by ip (Li et al, 2013;Unal et al, 2013) and by sc administration (He et al, 2009), suggesting that the plasma concentrations at these dose levels are comparable. However, ip morphine at 3 and 10 mg/kg decreases the response rates to approximately 80 and 50%, respectively, but not at 0.3 and 1 mg/kg (Morgan et al, 1999), and slight sedation is noted in some rats in our laboratory (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…The sc morphine generalized to the training dose of morphine at 3 mg/kg, and the po morphine generalized at 10-fold this dose level (30 mg/kg). In discrimination training, sc morphine at 3 mg/kg is a commonly used route and dose combination, as is ip administration at this dose (Nishida et al, 1989;Easterling and Holtzman, 1998;Li et al, 2013). This means that sc morphine at 3 mg/kg induces sufficient discrimination stimulus effects.…”
Section: Discussionmentioning
confidence: 99%